COMMUNITY-BASED TOURISM PRACTICES IN THE COMMUNITIES OF CÓRREGO DO SAL AND BARRINHA, IN ICAPUÍ - Branco, Carolina Anselmo Castelo; Santos, Antônia Maxwelle Paz; Maciel, Harine Matos; Sobreira, Patrícia; Gomes, Maria Antunizia; Feitosa, Anny Kariny; Machado, Érica Priscilla Carvalho de Lima; Maciel, Wlisses Matos; Branco, Camila Silva Castelo (Seven Editora, 2026)
The present study aims to examine community-based tourism in the communities of Córrego do Sal and Barrinha, located in the municipality of Icapuí, with the objective of analyzing how community-based tourism is developed in these areas. Tourism encompasses various typologies, and community-based tourism is one of them. It is characterized by being developed by residents of a given region, with the objective of organizing and controlling local productivity and generating income through tourism. In this context, the article focuses on community-based tourism practices in Córrego do Sal and Barrinha, investigating experiences and local dynamics supported by partnerships such as Fundação Brasil Cidadão, Fundação AVINA, Fundação O Boticário, and Banco Santander. The methodology applied consisted of a bibliographic review, based on authors such as Coriolano, Borges, Maldonado, Mollison, Sancho, and Soares, and field research using a semi-structured questionnaire administered to the local community. Córrego do Sal and Barrinha were selected as case studies due to their tourism potential oriented toward community-based tourism. The research demonstrated that, through the practice of community-based tourism and the encouragement of local participation as both actors and entrepreneurs, the region developed initiatives such as the Mulheres Alimentando Vidas group and the Mulheres de Corpo e Alga group, which contribute to the growth of community-based tourism by generating employment and income for the local population, while also attracting tourists interested in experiencing this type of tourism that promotes the destination while preserving it. Understanding the community-based practices implemented in these communities is relevant for identifying successful models that can be adapted and promoted in other locations as a means of fostering local economic and social development, making residents the driving force behind these initiatives.